Analisis Efisiensi Produksi dan Kualitas Pemotongan Mesin Ring Cup Plastik - Samsura, DT Alvin Tamimi Ramadhan; Butarbutar, Elky Gunawan; Hermanto, Tino (CV. IRA PUBLISHING, 2025)
Abstract This study aims to analyze the efficiency and cutting quality of a plastic ring cup cutting machine as a solution to the manual separation process, which is time-consuming and less effective. An experimental test was conducted using a cutting machine with a design capacity of 100 kg/hour and a 1 hp electric motor operating at a speed of 627.2 rpm. The testing focused on production capacity efficiency, cutting time, accuracy, and the quality of the cut. From ten trials, the average actual output was 44.69 kg/hour with an efficiency of 44.69% compared to its maximum capacity. These results indicate that several factors, including blade sharpness, machine size, and operational conditions, influence the machine’s performance. In terms of quality, some samples showed rough or incomplete cuts due to reduced blade sharpness. Nevertheless, the cutting machine proved capable of significantly improving the speed and efficiency of plastic waste processing on a small scale. With design improvements and proper blade maintenance, the machine’s performance can be optimized, making it a practical and environmentally friendly alternative for plastic waste processing equipment.